Integration of technical knowledge as a way of forming of professional competence of students of technical university - Gabdrakhmanova, K. F. (My University, 2014)
The article describes ways and methods of improving the quality of graduation in Oil and Gas Engineering by means of implementation of the competence building approach within the modernization of the content of professional education. The article proves the expediency of use of the activity approach in formation of professional competence of students of technical University and the experience of implementing this approach. The author emphasizes the importance of the discipline of mathematics in its function as the basis of professional education and pays special attention to the determination of the types of competences and the formation of general professional skills of bachelors. The article deals with the basic concepts of the «task» and the author's understanding of the term «task». The author presented the experience of the development of practice - oriented tasks for students of technical University. The article also considers the experience of implementation of this technology at studying mathematics at the Petroleum Technological University in compliance with the requirements of the third generation standards. The technology of professional competences formation is offered. Special attention is paid to the technology of formation of professional competence of students of technical University. In this article, stages of organization of the study process at implementation of the technology of the problem-based approach in the education are provided. Specific examples are considered methods of organizing the formation of professional competences. The author reveals the subject matter of a mathematical problem in its function as the basic means of competence formation with the students of technical higher education institutions shows the relevance of treatment in learning process task approach and suggests specific methodology for forming key competences through solving technological problems.
Keywords: professional competence; basic concepts of professional training of future engineers; a problem in its function as the means of forming professional competences